Effectiveness of life skills education and psychoeducation on emotional and behavioral problems among adolescents in institutional care in Kenya: a longitudinal study. Issue 4 (25th July 2017) - Mutiso, Victoria; Tele, Albert; Musyimi, Christine; Gitonga, Isaiah; Musau, Abednego; Ndetei, David
Abstract : Background: This study aimed to test the effectiveness of life skills education (LSE) and psychoeducation in the reduction of Youth Self Report (YSR) scores on institutionalized children using structured activities supported by trained facilitators. LSE involved participation of children in life skills activities to support development of key psychosocial competencies and interpersonal skills. Methods: The study included 630 children from three institutions. Of these, 171 were in the Intervention Group 1 (life skills education and psychoeducation), 162 were in the Intervention Group 2 (psychoeducation only), and 297 children were in the control group. A researcher‐developed socio‐demographic questionnaire and the YSR were used. Baseline assessments were conducted before the interventions and again at 3, 6, and 9 months. Differences between the two intervention groups and the control group were investigated using least squares linear regression. Results: There was a statistically significant reduction in scores in internalizing, externalizing, and total problem scores in both intervention arms ( p  < .05) compared with the control arm at 3 months. At 6 months, no significant differences were found between the intervention Group 1 and control group for internalizing score ( p  = .594); however, there were significant differences in both intervention groups for both externalizing and total problem scores ( p  < .05). At 9 months, significant differences were observed between control and both intervention groups for externalizing scores; total problems for Intervention Group 1. Conclusions: A combination of Life Skills Education and psychoeducation is effective in reducing emotional and behavioral problems in institutionalized children.